Microwave-assisted biosynthesis and characterization of ZnO film for photocatalytic application in methylene blue degradation - Sulistyo Rini, Ari; Nabilla, Averin; Rati, Yolanda (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2021)
This study aims to investigate the physical characteristics and photocatalyst activity of biosynthesized ZnO with pineapple (Ananas comosus) peel extract under microwave irradiation. The ZnO powder was prepared in two different concentrations of zinc nitrate hexahydrate (ZNH) at 200mM (Z-200) and 500 mM (Z-500). The optical, structural, and morphological properties of ZnO were analyzed using UV-Vis spectroscopy, X-Ray Diffraction (XRD), and Scanning Electron Microscopy (SEM), respectively. The UV-Vis absorption spectrum showed a wide absorbance peak of ZnO at the wavelength of 300-360 nm with a bandgap energy of 3.22 and 3.25 eV. The XRD result confirmed the wurtzite structure of ZnO with high crystallinity. SEM morphology showed spherical particles with an average particle size of 190-220 nm. For photocatalytic application, ZnO film was fabricated via the doctor blade method from microwave-assisted biosynthesized ZnO powder. ZnO films were then applied under UV-irradiation to examine the photocatalytic degradation of methylene blue. It was found that the catalytic behavior of ZnO film was affected by the starting ZNH concentration with maximum effectiveness of 46% degradation after 2 h.